Education Leadership in The Establishment of The Nation's Reserve Components - Almubaroq, Hikmat Zakky (JURNAL AL-TANZIM, 2022)
This study aims to analyze and understand educational leadership in shaping the nation's reserve component at the Defense University of the Republic of Indonesia. This research uses a qualitative case study, where the researcher uses interviews, observations, and documentation to obtain accurate data. The data analysis was carried out circularly, starting from data collection, presentation, reduction, and conclusions. The results of the study indicate that the national reserve component program at the Defense University of the Republic of Indonesia uses the involvement of educational leadership in totality which is carried out through; exemplary transformational leaders, leadership, builds self-confidence, futuristic leadership, strengthens the code of ethics of local wisdom. This research has implications for the importance of establishing the nation's reserve component through leadership education from an early age to be able to foster the enthusiasm of the entire academic community in involving its potential as a component of the nation's reserves that can assist the main component in strengthening the nation's defense.